Urgensi Manajemen Talenta ASN Melalui Kolaborasi di Kementerian Kelautan dan Perikanan - Andriansyah; Asropi (PT. Alahyan Publisher Sukabumi, 2026)
Talent management is a strategic instrument to ensure the availability of competent, high-performing, integrity-driven, adaptive, and future-ready civil servants for strategic positions within the Ministry of Marine Affairs and Fisheries. This study aims to analyze the urgency of talent management at the Ministry of Marine Affairs and Fisheries with a focus on collaboration in talent development. The research applies a qualitative-descriptive approach through literature review and policy document analysis without changing the theoretical framework of talent management, merit systems, strategic human resource management, and public sector collaboration. The findings show that talent management is urgent for strengthening succession planning, reinforcing the merit system, reducing fragmentation in competency development, and improving civil service readiness to respond to the complexity of the marine and fisheries sector. Collaboration is a determining factor because talent development requires the integration of competency, performance, potential, critical-position needs, learning curricula, mentoring, strategic assignments, and placement mechanisms. This study recommends strengthening a collaborative talent development ecosystem through a cross-echelon forum, integration of Corporate University with the talent pool, leadership mentoring, experiential learning, and strategic external partnerships.